Pengembangan Media Sosial dalam Pelayanan Library 2.0 di Perpustakaan Akademi Keperawatan Notokusumo Yogyakarta - Ahmad Anwar (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
This study explains about social media development in the library 2.0 service based on Akademi Keperawatan Notokusumo Yogyakarta Library experience. The development of library 2.0 service aims to resolve the distance problem of library service. This study uses qualitative method with action research approach. From the research strategy, it shows that people are easier to be connected with social media Instagram rather than the others. However, the obstacle of this development comes from the librarians who are less experience to deal with social media owned by the library. The best solution is by holding some training in advance of social media management and social media communication.Keywords: Library 2.0, Social Media, Library Service